Age‐ and Sex‐Dependent Changes of Intra‐articular Cortical and Trabecular Bone Structure and the Effects of Rheumatoid Arthritis. (18th November 2016) - Simon, David; Kleyer, Arnd; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Hueber, Axel J; Haschka, Judith; Renner, Nina; Figueiredo, Camille; Neuhuber, Winfried; Buder, Thomas; Englbrecht, Matthias; et al.
ABSTRACT: The objective of this cross‐sectional study was to define normal sex‐ and age‐dependent values of intra‐articular bone mass and microstructures in the metacarpal heads of healthy individuals by high‐resolution peripheral quantitative computed tomography (HR‐pQCT) and test the effect of rheumatoid arthritis (RA) on these parameters. Human cadaveric metacarpal heads were used to exactly define intra‐articular bone. Healthy individuals of different sex and age categories and RA patients with similar age and sex distribution received HR‐pQCT scans of the second metacarpal head and the radius. Total, cortical, and trabecular bone densities as well as microstructural parameters were compared between 1) the different ages and sexes in healthy individuals; 2) between metacarpal heads and the radius; and 3) between healthy individuals and RA patients. The cadaveric study allowed exact definition of the intra‐articular (intracapsular) bone margins. These data were applied in measuring intra‐articular and radial bone parameters in 214 women and men (108 healthy individuals, 106 RA patients). Correlations between intra‐articular and radial bone parameters were good ( r  = 0.51 to 0.62, p  < 0.001). In contrast to radial bone, intra‐articular bone remained stable until age 60 years (between 297 and 312 mg HA/cm 3 ) but decreased significantly ( p  < 0.001) in women thereafter (237.5 ± 44.3) with loss of both cortical and trabecular bone. Similarly, RA patients showed significant ( p  < 0.001) loss of intra‐articular total (263.0 ± 44.8), trabecular (171.2 ± 35.6), and cortical bone (610.2 ± 62.0) compared with sex‐ and age‐adjusted controls. Standard sex‐ and age‐dependent values for physiological intra‐articular bone were defined. Postmenopausal state and RA led to significant decrease of intra‐articular bone. © 2016 American Society for Bone and Mineral Research.